Improving Energy Efficiency with Reusage Outlet Stream of Heat Exchanger for Acrylic Acid Production from Propylene Oxidation - Nasywa Aprilia Deanti; Alexander Nathanael Owen; Christine Elisha Simarmata; Jananda Kristian Sidabukke; Muhammad Aymanhadi Maulana Almasyah; Sarah Agnesia Silaen (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Acrylic acid is a pivotal chemical intermediate extensively utilized in the manufacture of superabsorbent polymers, coatings, adhesives, and acrylate esters. Conventional production via propylene oxidation is markedly energy intensive and generates substantial by products, highlighting the imperative for process enhancement. The objective of this study is to advance energy efficiency in acrylic acid synthesis by reusing outlet stream heat from the heat exchanger during propylene oxidation. Aspen Plus simulations were employed to model propylene oxidation in a plug flow reactor under isothermal conditions with external cooling. The revised design incorporated heat integration strategies, most notably redirecting surplus heat from heater H-302 to fulfill the reboiler duty of distillation column T-304. Comparative evaluation demonstrated that this modification reduces external energy demand, augments conversion efficiency, and stabilizes thermal performance. In addition, the implementation of a heat transfer fluid recycle loop curtailed energy losses and enhanced operational consistency across both reactor and separation units. Mass and energy balance analyses confirmed that the modified configuration delivers superior efficiency while diminishing reliance on external utilities. Collectively, the findings underscore that process intensification coupled with heat integration provides a more sustainable and economically advantageous pathway for acrylic acid production. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).